THE CONTRIBUTION OF PHILIPPE BAUMARD TO THE DEVELOPMENT OF ECONOMIC INTELLIGENCE THEORY AND STRATEGIC CULTURE IN FRANCE - Kopitić, Njegoš; Milenković , Sofija (Political Review, 2026)
Research on knowledge management, organizational dynamics, and crisis decision-making in France has been profoundly influenced by the cognitive theory of Philippe Baumard. By emphasizing the strategic interconnection between the economy and the state, Baumard pioneered an original framework for economic intelligence, transposing knowledge and practices from the national intelligence and security community (communauté nationale du renseignement – [CNR]) into the domains of business, large capital, and the private sector. In parallel, he contributed to the development of French strategic culture, addressing existing gaps through reliance on strategic information and defense traditions. Advocating a proactive approach centered on sovereignty and the protection of economic interests, Baumard initiated efforts to position France as a global economic power capable of maintaining independence in an increasingly competitive environment. His contributions extended to cybersecurity, where he distinguished himself both as a systems theorist and as a practitioner. Despite the significance of his work, Baumard’s theoretical and practical contributions remain largely unfamiliar to the broader professional community. This study, through qualitative analysis of documentary sources, underscores the interdisciplinary and comprehensive nature of his approach – rooted in the political traditions of Charles de Gaulle and bearing implications across strategy, economy, intelligence, education, and cybersecurity. The findings suggest that Baumard’s scholarship provides a valuable foundation for advancing the understanding of national power, strategic culture, and the role of economic intelligence in contemporary global competition.